Analysis Of Legal Protection Of Intellectual Property Rights On Batu Bara Songket Cloth In Batu Bara Regency - Imam Rizky Fahreza (jurnal.unprimdn.ac.id, 2025)
This study aims to examine the urgency of legal protection for Songket Batu Bara cloth within the framework of intellectual property law, with an emphasis on its recognition as a Traditional Cultural Expression (EBT) that receives legal protection based on the provisions of Law Number 28 of 2014 concerning Copyright. Songket Batu Bara cloth is a cultural product of the Malay community that is full of historical, artistic, and philosophical values, and is passed down from generation to generation. Typical motifs such as bamboo shoots, cananga flowers, and pandan shoots contain deep symbolic meanings and socio-cultural functions. This study uses a normative juridical method with a statutory regulatory approach and a conceptual approach, to analyze the positive legal norms that form the basis for the protection of this traditional cultural work. The results of the study indicate that legal protection for Songket Batu Bara is not optimal due to obstacles in the aspects of legal substance, institutional structure, and legal culture of the community. The absence of specific technical regulations, the weak role of related institutions such as the DJKI and regional offices, and low legal awareness among craftsmen are the main inhibiting factors. Therefore, it is necessary to formulate affirmative policies by local governments through regional regulations, strengthening the institutions of artisan communities, and synergy between academics, the private sector, and the community to realize an effective, adaptive, and sustainable intellectual property rights protection system.